Pengaruh Komunikasi Yang Efektif Oleh Guru Pendidikan Agama Kristen Terhadap Karakter Kekristenan Siswa Kelas VIII SMP Negeri 4 Laguboti Kabupaten Toba Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to find out how much influence Effective Communication by Christian Religious Education Teachers has on the Christian Character of students at SMP Negeri 4 Laguboti for the 2023/2024 Academic Year. The research method used is a descriptive quantitative research method. The population is all students in class VIII of SMP Negeri 4 Laguboti consisting of 6 classes totaling 190 students and a sample of 33 people was determined using a probability sampling technique with a random type (simple random sampling). Data was collected using a positive closed questionnaire with 25 items, namely 15 items for variable : 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.598 > rtable(a=0.05,n=33) = 0.344. b) Testing a significant relationship obtained a value of tcount= 4.135 > ttable(a=0.05, dk=n-2=31)= 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y=10.81+0.46X. b) Regression coefficient of determination test (r2) = 35.7%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=15, dk denominator=n-2=33-2=31) namely 17.24 > 2.01. Thus Ha is accepted and H0 is rejected.